An Investigation Of Job Burnout And Motivation Factors In China Higher Vocational College - Chen, Wen Jie (2021)
Burnout is a continuous, hostile, work-related state, including mental, emotional, or physical exhaustion. Teacher burnout has been a significant concern of mainstream education in recent years. However, there is little research on it among Chinese higher vocational teachers. Therefore, this study adopts a mixed method sequential design by (a) determining the characteristics of job burnout and motivation of some Chinese higher vocational teachers, (b) examining the (possible) relationship between their job burnout and teaching motivation, and (c) ) Investigate the motivational factors that predict teacher burnout to fill this gap. To this end, 151 English teachers from China’s Yunnan Province participated in the study. In order to collect data, the Maslach job burnout questionnaire compiled by Maslach and Jackson (1986) and the teaching motivation questionnaire compiled by Gagné (2015) and Tremblay (2009) were used to conduct random sampling surveys. Descriptive statistics show that job burnout of higher vocational teachers is low, and they have autonomy in teaching. Correlation analysis also reveals that the motivation of higher vocational teachers is negatively correlated with job burnout. In addition, multiple regression analysis shows that autonomous forms of motivation can better predict the job burnout of higher vocational teachers. This article provides some enlightenments for decision-makers in the field of higher vocational education to improve the motivation of higher vocational teachers for autonomous learning and reduce their burnout experience.